Pediatric nursing : caring for children and their families - Potts, Nicki L.; Mandleco, Barbara L. (Australia, Singapore : Thomson/Delmar ; Thomson Learning Asia, 2002)
A comprehensive text for undergraduate nursing students that approaches the topic of children's health care from a holistic and family-centered perspective.
Unit I: Pediatric nursing in a changing society -- Unit II: Growth and development of children -- Unit III: Unique considerations in children -- Unit IV: Alterations in nutrition and elimination -- Unit V: Alterations in oxygen transport -- Unit VI: Alterations in protective mechanisms -- Unit VII: Alterations in sensorimotor function -- Unit VIII: Other alterations to children's health
Includes index.
Keywords: PEDIATRIC NURSING